2015
DOI: 10.1111/1751-7915.12245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of industrial Saccharomyces cerevisiae strains as the chassis cell for second‐generation bioethanol production

Abstract: To develop a suitable Saccharomyces cerevisiae industrial strain as a chassis cell for ethanol production using lignocellulosic materials, 32 wild-type strains were evaluated for their glucose fermenting ability, their tolerance to the stresses they might encounter in lignocellulosic hydrolysate fermentation and their genetic background for pentose metabolism. The strain BSIF, isolated from tropical fruit in Thailand, was selected out of the distinctly different strains studied for its promising characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 35 publications
(51 reference statements)
2
49
0
Order By: Relevance
“…Considering stress conditions involved in the fermentation processes for the production of 2G ethanol (Costa et al, 2014;Li et al, 2015), the sixteen isolates that showed tolerance to ethanol and were selected had different degrees of tolerance (Table 2), but none of those tolerated all the conditions imposed. This information is corroborated by Li et al (2015), where none of the five strains of S. cerevisiae tolerated all …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering stress conditions involved in the fermentation processes for the production of 2G ethanol (Costa et al, 2014;Li et al, 2015), the sixteen isolates that showed tolerance to ethanol and were selected had different degrees of tolerance (Table 2), but none of those tolerated all the conditions imposed. This information is corroborated by Li et al (2015), where none of the five strains of S. cerevisiae tolerated all …”
Section: Discussionmentioning
confidence: 99%
“…The conditions tested respectively were: Glucose (35% and 50%), hyperosmotic stresses (10 and 16% KCl), acetic acid (0.5 and 1%), temperatures of 42 and 50°C, vanillin (6 and 8 μmol.L -1 ), furfural (0.25, 0.5, 1.0 and 1.2 g.L -1 ) and oxidative stress. Also concentrations of cellobiose 1% and arabinose 1% (Ali and Khan, 2014;Li et al, 2015) were tested. For this, the strains were previously cultured overnight in YEPD agar medium (composition/L: 10 g yeast extract, 20 g peptone, 20 g dextrose, and 20 g agar, 1000 mL distilled water) and washed twice with sterile water.…”
Section: Tolerance Testsmentioning
confidence: 99%
“…Ethanol fermentation strain Saccharomyces cerevisiae XH7 was an engineered strain from the wild diploid Saccharomyces cerevisiae BSIF (Li et al 2015). The strain was cultured in YPD medium containing 20 g/L of glucose, 20 g/L of peptone, and 10 g/L of yeast extract.…”
Section: Strains and Mediummentioning
confidence: 99%
“…The growth of most robust microbe for fermentation, Saccharomyces cerevisiae, was inhibited by compounds resulted from lignocelullosic hydrolisate such as aldehydes, ketones, phenols and organic acids (Palmqvist and Hahn-Hagerdal 2000;Li et al 2015). These inhibitory aldehyde compounds have been given more attention during the last two decades due to their toxicity to the fermentative microbe's cells.…”
Section: Introductionmentioning
confidence: 99%